PROFESSIONAL TRAINING OF PHYSICAL CULTURE TEACHERS FOR USE IN NATIONAL MARTIAL ARTS CAREER - A.L. Prytula (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : analysis of the problem of training the future teachers of physical education to the use of the national martial arts career. The objectives of the study was to develop and validate the content of the training of future specialists of physical culture and sports. The basis of preparation of the content is put on the Ukrainian fighting saved. Material : The study involved 242 students, 88 teachers. Results : determine the appropriateness of the training of future specialists in Ukrainian fighting SPAS four groups of methods: the organization and implementation of the educational-cognitive activity of students; stimulating learning activities; control and self-learning; the formation of social behavior. It is proved that the practical training must be systematic and consist of the following stages: laboratory and practical classes; educational practice coaches, technological practice directly in organizations and institutions. Conclusions : It was determined that a promising direction for future development of professional training coaches is that the interests of the individual and its support in the development process. This will lead to the satisfaction of needs experienced personnel specialists in national martial arts.